Understanding Adolescents and Teachers at Vocational Schools From a Health Promotion Perspective - Margit Dall Aaslyng; Jacob Suhr Bisschop-Thomsen; Liv Juncker Harsløf (SAGE Open)
Students at vocational schools in Denmark have, on average, a lower health status than that of comparable young people in high schools for several parameters. Against this background, several health-promoting activities have been initiated at vocational schools. However, the problem is persistent, and therefore a new approach is needed developed on the basis of an understanding of the target group. The aim was to gain understanding of students and teachers in vocational schools by creating personas. The personas were based on observational data ( n  = 7 classes) and semi-structured interviews among students ( n  = 22) and teachers ( n  = 7). The interviews with the students explored aspects related to health, school, well-being, and eating habits, while the teacher interviews were aimed at gaining a better understanding of their role in health promotion practice at the vocational schools. Four different student personas and three different teacher personas were created. The four student personas showed that health can be perceived in four different ways: as quality of life, absence of disease, following official recommendations and healthism. The personas describe the broad spectrum of students at vocational schools. They address the insight we gained during our analysis that health interventions should be multicomponent, targeting several aspects of health and several types of students. The three teacher personas showed that teaching health as part of a vocational education requires personal authenticity and a specific set of pedagogy and didactics. Our teacher personas address the fact that teachers are key persons in developing health promotion practices at vocational schools.